Monomodal linear low density ethylene / 1-butene copolymers
By using a single peak linear low-density ethylene/1-butene copolymer prepared by bridged bis(tetrahydroindenyl)zirconium dicetyl catalyst, the problem of difficult tearability of the plastic film in the longitudinal and transverse directions is solved, and the film is highly oriented tear and good melt processability is achieved, and it is suitable for packaging and container applications.
Patent Information
- Application Number
- CN202280098904.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-31
- Publication Date
- 2025-05-30
AI Technical Summary
The tearability of existing plastic films in the longitudinal and transverse directions is difficult to control, resulting in possible material losses in packaging and container linings.
A single peak linear low-density ethylene/1-butene copolymer (C4-uLLDPE) and a post-reactor blend were used to copolymerize ethylene and 1-butene by a bridged bis(tetrahydroindenyl)zirconium dicetyl catalyst to prepare a film with improved directional tear.
The film is achieved with high directional tear in the longitudinal direction without damaging the melt processability or overall toughness, can effectively avoid material losses, and is suitable for a variety of packaging and container applications.
Smart Images

Figure CN120077078A_ABST
Abstract
Description
Technical Field
[0001] Polyethylene, polyolefin blends, plastic films, polymerization processes and methods. Background Art
[0002] Patent application publications and patents in this field or related to this field include U.S. Patent Nos. US 4,781,297; US 5,336,746; US 5,466,649; US 5,525,689; US 5,374,700; US 5,639,842; US 5,712,352; US 5,763,543; US 6,476,171B1; US 6,870,010B1; US 8,957,159B2; US 10,370,469B2; and US 10,508,164B2; and U.S. Patent Application Publication Nos. US2005 / 0100753A1 and US2021 / 0070902A1. Summary of the Invention
[0003] Most plastic films are slightly more prone to tearing in the machine direction (MD) - the direction in which the film advances as it exits the film extruder die (see the MD arrow in Figure 1 ), and its opposite or "reverse machine" direction, which is opposite to the MD arrow in Figure 1 - than in the cross direction (CD, sometimes also referred to as the transverse direction (TD)) - the side-to-side direction perpendicular to the MD direction (see the CD arrow in Figure 1 for one side-to-side direction). The tear direction of these films cannot be controlled. In bags, packaging, and container liners (such as box or drum liners), this lack of directional tear control can result in the loss of the material contained inside.
[0004] One challenge in the plastic film industry is to find new films with high directional tear resistance. Simply put, this means that such films are significantly more prone to tearing longitudinally than transversely. This lower tear resistance in one direction relative to the other will provide an advantage to the end user. For example, if the tear resistance in the longitudinal direction is high enough (i.e., the tear resistance is low enough), and the tear resistance in the transverse direction is high enough (low CD tear resistance), then end users such as consumers will be able to tear open bags, packaging, or container liners by hand without the aid of a cutting blade and without losing the material contained inside.
[0005] One way to attempt this is to take a reference film and vary its resin composition to try to selectively increase its longitudinal tearability while minimizing the increase in transverse tearability. This is easier said than done because blown film properties depend on a three-legged stool balance of properties including resin melt processability, film orientation tearability, and overall film toughness. If the orientation tearability is increased, the melt processability and / or overall film toughness will typically undesirably decrease. This can lead to blown film defects such as bubble instability, thickness variations, wrinkles, lines, a rough surface due to melt fracture, holes, or tears.
[0006] A new linear low density polyethylene (LLDPE) resin has been discovered that can be used to make blown LLDPE films that have this improved (increased) orientation tearability without sacrificing melt processability or overall toughness. The new LLDPE films are easy to tear in the machine direction (MD) or reverse machine direction (opposite the MD), but difficult to tear in the cross direction (CD) or reverse cross direction. The new LLDPE resin has sufficient melt processability to enable its use on single layer and multilayer film blowing production lines under standard blown film conditions to form new LLDPE films without defects. The new LLDPE films have overall toughness such that they can withstand normal abuse during end use operations (e.g., packaging operations such as wrapping a pallet of boxes with the film) as well as the transportation and disposal of the end use product (e.g., transporting and disposing of a pallet of goods wrapped). The new LLDPE films have good optical clarity and haze. The following embodiments of the invention include:
[0007] A unimodal linear low density ethylene / 1-butene copolymer (“C4-uLLDPE”) prepared by copolymerizing ethylene and 1-butene using a bridged bis(tetrahydroindenyl)zirconocene catalyst.
[0008] A post-reactor blend comprising the unimodal linear low density ethylene / 1-butene copolymer (“C4-uLLDPE”) and a different polyolefin polymer.
[0009] A method of making a film comprising the unimodal linear low density ethylene / 1-butene copolymer (“C4-uLLDPE”) or the post-reactor blend.
[0010] A film comprising the unimodal linear low density ethylene / 1-butene copolymer (“C4-uLLDPE”) or the post-reactor blend. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1View of a single-layer film roll, the single-layer film being shown as partially unrolled (or not fully rolled up), where the vertical arrows illustrate the machine direction (MD) and the cross direction (CD).
[0012] Figure 2 Diagram of the chain structures of LLDPE, LDPE, and HDPE.
[0013] Figure 3 Schematic cross-sectional view of a multilayer film structure including three film layers.
[0014] Figure 4 Schematic cross-sectional view of a multilayer film structure including seven film layers. Detailed Description
[0015] Activator (for metallocene pre-catalyst): Lewis acid, non-coordinating ionic activator, or ionizing activator, or Lewis base, alkylaluminum, or alkylaluminoxane. The activator can be methylaluminoxane (MAO), ethylaluminoxane, 2-methylpropylaluminoxane, or modified methylaluminoxane (MMAO). The molar ratio of aluminum of the activator to zirconium of the bridged bis(tetrahydroindenyl)zirconocene pre-catalyst (Al / Zr molar ratio) can be from 1000:1 to 0.5:1, alternatively from 300:1 to 1:1, alternatively from 150:1 to 1:1.
[0016] 1-Butene or "C 4 ": A compound of the formula H 2 C=CHCH 2 CH 3 .
[0017] Ethylene or "C 2 ": A compound of the formula H 2 C=CH 2 .
[0018] Film: A continuous layer of polymeric material with a thickness greater than 5 micrometers (μm) to 250 μm, as defined by ASTM terminology D883. The film thickness is measured in accordance with ASTM D6988-21, Standard Guide for Determination of Thickness of Plastic Film Test Specimens.
[0019] 1-Hexene or "C 6 ": A compound of the formula H 2 C=CHCH 2 CH 2 CH 2 CH 3compounds.
[0020] In the reactor: occurs during the polymerization process and at a location inside the polymerization reactor.
[0021] In-reactor blend: a mixture prepared in a polymerization reactor by in-situ preparation of a second polymer in the presence of a first polymer in the polymerization reactor, and wherein the first polymer is prepared before the second polymer or the first polymer and the second polymer are prepared simultaneously together.
[0022] LLDPE (linear low density polyethylene) vs LDPE (low density polyethylene) vs HDPE (high density polyethylene). These polyethylenes have different polymer chain structures, as Figure 2 illustrated in the figure, and are the result of different polymerization process conditions and initiators or catalysts used to prepare them. Generally, the difference between LLDPE and LDPE lies in the polymerization process conditions and initiators or catalysts used to prepare them, which results in a difference in the amount of long chain branching. LDPE is prepared by a free radical polymerization process under high pressure (e.g., initiated by a small amount of organic peroxide), and thus LDPE inherently has a large amount of long chain branching, as Figure 2 shown. Previous LLDPE was prepared using a conventional Ziegler-Natta catalyst, which does not produce long chain branching, and thus previous LLDPE was linear and had no long chain branching, as Figure 2 exemplified. Generally, the difference between LLDPE and HDPE lies in the density and the amount of short chain branching (SCB). LLDPE has a density less than 0.940 g / cm 3 , while HDPE has a density greater than or equal to 0.940 g / cm 3 . Moreover, LLDPE has a large amount of short chain branching, while HDPE has a much smaller amount of short chain branching, as Figure 2 shown.
[0023] Kurtosis or (prefix)-kurtic refers to the property of the distribution of polymer molecular weights in a plot of dW / dLog(MW) on the y-axis versus Log(MW) on the x-axis above a molecular weight of 1,000 grams per mole (Log(MW) > 3.0) to provide a gel permeation chromatography (GPC) chromatogram, where Log(MW) and dW / dLog(MW) are as defined herein and are measured by the high temperature gel permeation chromatography (GPC) test method described later. Kurtosis can be unimodal or multimodal, and multimodality can be bimodal, trimodal, or higher. A unimodal molecular weight distribution is characterized by one and only one GPC peak. A multimodal MWD is characterized by two or more peaks. When a multimodal MWD has two and only two peaks, it is bimodal (bimodal MWD). Any two peaks in a multimodal MWD can be separated by a distinguishable local minimum therebetween, or one peak can be only a shoulder on another peak.
[0024] Precatalyst: A catalyst precursor that produces a catalyst when contacted with an activator.
[0025] Ziegler-Natta catalyst: Typically a titanium catalyst supported on magnesium dichloride solid and optionally silica. The catalyst is prepared by contacting a Ziegler-Natta precatalyst with a suitable activator, which is different from the activator used for metallocenes. A typical Ziegler-Natta (pre)catalyst comprises a titanium(IV) compound (e.g., Ti(O-isopropyl) 2 ) or TiCl 4 supported on a magnesium halide (e.g., MgCl 4 ) solid and optionally hydrophobic pyrogenic silica (e.g., Cab-O-Sil TS-610). The precatalyst can be unmodified (i.e., without modifier compounds), or the Ziegler-Natta (pre)catalyst can be modified with modifier compounds. Modifier compounds can be unsubstituted ethers, unsubstituted alcohols, or combinations thereof; e.g., tetrahydrofuran, ethanol, or a combination of tetrahydrofuran (“THF”) and ethanol (“EtOH”). Ziegler-Natta catalysts generally give polyethylene a broader molecular weight distribution (higher polydispersity index value) than metallocene catalysts.
[0026] One embodiment is a unimodal linear low density ethylene / 1-butene copolymer (“the C4-uLLDPE of the present invention” or simply “C4-uLLDPE”), which is prepared by copolymerizing ethylene and 1-butene using a bridged bis(tetrahydroindenyl)zirconocene catalyst selected from the group consisting of: ethylenebis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, ethylenebis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl, dimethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, dimethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl, diphenylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, diphenylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl, diethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dichloride and diethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl; wherein the unimodal linear low density ethylene / 1-butene copolymer is characterized by each of the following properties: a density of from 0.915 grams per cubic centimeter (g / cm 3 ) to 0.939 g / cm 3 measured according to Method B of ASTM D792-13; a melt index (I 2 ) of from 0.1 grams per 10 minutes (g / 10 min.) to 4.0 g / 10 min. measured according to ASTM D1238-13 at 190 °C / 2.16 kg; and a polydispersity index M w / M n of from 3.0 to 5.0 measured according to the high temperature gel permeation chromatography (GPC) test method in the specification. C4-uLLDPE can be prepared by copolymerizing ethylene and 1-butene using a bridged bis(tetrahydroindenyl)zirconocene catalyst in a gas phase polymerization reactor such as a fluidized bed gas phase polymerization reactor described later. Another chemical name for C4-uLLDPE is unimodal linear low density poly(ethylene-co-1-butene) copolymer.
[0027] C4-uLLDPE can have a density of from 0.921 g / cm 3 to 0.939 g / cm 3 , alternatively from 0.921 g / cm 3 to 0.929 g / cm 3 , alternatively from 0.920 g / cm 3 to 0.924 g / cm 3 , alternatively from 0.926 g / cm 3 to 0.930 g / cm 3 , alternatively from 0.935 g / cm 3 to 0.939 g / cm 3Density. The density is measured according to ASTM D792-13, Method B.
[0028] C4-uLLDPE may have a melt index (I 2 ) of from 0.2 g / 10 min. to 1.4 g / 10 min., alternatively from 0.2 g / 10 min. to 0.7 g / 10 min., alternatively from 0.8 g / 10 min. to 1.2 g / 10 min. The melt index (I 2 ) is measured according to ASTM D1238-13 using the conditions of 190 °C / 2.16 kg.
[0029] C4-uLLDPE may have a polydispersity index M w / M n of from 3.5 to 4.5, alternatively from 3.6 to 4.1, alternatively from 3.9 to 4.4, alternatively from 3.5 to 3.9, alternatively from 3.8 to 4.2, alternatively from 4.1 to 4.5. M w is the weight-average molecular weight and M n is the number-average molecular weight, and the M w value and the M n value are measured according to the high-temperature gel permeation chromatography (GPC) test method described later.
[0030] The content of long-chain branches per 1000 carbon atoms (content / 1000C) of C4-uLLDPE measured by carbon-13 nuclear magnetic resonance ( 13 C-NMR) spectroscopy according to the long-chain branching (LCB) value test method in the specification may be from 0.005 to 0.050, alternatively from 0.015 / 1000C to 0.034 / 1000C, alternatively from 0.020 / 1000C to 0.030 / 1000C. As used herein, having an LCB content means having an amount of long-chain branching detectable by 13 C-NMR spectroscopy, which currently has a detection limit of 0.004 / 1000C. LCB contents from greater than 0.000 to less than 0.005 are excluded herein.
[0031] C4-uLLDPE may have at least one of the characteristics (i) to (iv): (i) a density of from 0.921 g / cm 3 to 0.939 g / cm 3 ; (ii) a melt index (I 2 ) of from 0.2 g / 10 min. to 1.4 g / 10 min.; (iii) a polydispersity index M w / M n; and (iv) a long chain branching content of from 0.005 / 1000 C to 0.050 / 1000 C. In some embodiments, the C4-uLLDPE can have any one of the combinations of properties (v) through (xii): (v) properties (i) and (ii); (vi) properties (i) and (iii); (vii) properties (i) and (iv); (viii) properties (ii) and (iii); (ix) properties (ii) and (iv); (x) properties (iii) and (iv); (xi) any three of properties (i) through (iv); and (xii) each of properties (i) through (iv).
[0032] Generally, if a conventional unimodal linear low density ethylene / 1-butene copolymer (conventional C4-uLLDPE) is to have sufficient melt processability properties to allow the conventional C4-uLLDPE to be melt blown into a film, the conventional C4-uLLDPE must have a broad polydispersity index M greater than 15 and more typically greater than 20 w / M n . These M w / M n requirements also apply to multimodal linear low density polyethylene which, due to its multimodality, naturally has a higher M w / M n value. In such conventional C4-uLLDPE, it is the broad molecular weight distribution of its polymer chains that achieves the desired melt processability. However, such a broad molecular weight distribution is not present in the C4-uLLDPE of the present invention. However, surprisingly, the C4-uLLDPE of the present invention does have sufficient melt processability properties such that the C4-uLLDPE of the present invention can be melt blown into the film of the present invention. Without being bound by theory, the inventors believe that the beneficial melt processability of the C4-uLLDPE of the present invention is due to the C4-uLLDPE of the present invention having a greater amount of long chain branching (LCB) content than conventional C4-uLLDPE, and this higher LCB content promotes melt processing into a blown film to some extent. It is believed that the higher LCB content is the result of the C4-uLLPDE of the present invention being prepared with a bridged bis(tetrahydroindenyl)zirconocene catalyst rather than an unbridged metallocene catalyst. Alternatively or additionally, the C4-uLLDPE can have a different type of long chain branching from the long chain branching of a comparative C6-uLLDPE copolymer. It is believed that the improved δ(SCBD) may also contribute to the improved processability of the C4-uLLDPE.
[0033] Optionally, in some embodiments, the C4-uLLDPE is characterized by at least one of the following properties: melt flow ratio (I 21 / I 2), the melt flow ratio is characterized by formula (A) described later; melt flow ratio (I 21 / I 2 ); high load melt index (I 21 ); improved δ(SCBD) determined by copolymer monomer content distribution analysis (iCCD) using the δ(SCBD) test method described later; composition distribution breadth index (CDBI) measured by iCCD; number average molecular weight (M N ); weight average molecular weight (M W ); or the ratio of M w / M n (polydispersity index).
[0034] The long chain branching (LCB) content of the C4-uLLDPE of the present invention can be directly or indirectly characterized by any one of the following measurement results (i) to (iii): (i) directly characterized by carbon-13 nuclear magnetic resonance (NMR) spectroscopy; (ii) indirectly characterized by the melt flow ratio (I 21 / I 2 ) formula described below; or (iii) indirectly characterized by the melt flow ratio (I 21 / I 2 ). In some embodiments, the characterization may include the combination of measurement results (i) and (ii), measurement results (i) and (iii), measurement results (ii) and (iii), or measurement results (i), (ii), and (iii). Measurement results (i) to (iii) and their ranges are described below.
[0035] In some embodiments, C4-uLLDPE can be characterized by at least one of the following melt flow ratios (I 21 / I 2 ): (i) melt flow ratio (I 21 / I 2 ), which is characterized by the following formula (A): melt flow ratio (I 21 / I 2 ) is greater than (-36.9 * melt index (I 2 )) + 68.0 (EQ. (A)), where * indicates multiplication, + indicates addition, and the symbol for "greater than" is >; (ii) melt flow ratio (I 21 / I 2 ), which is characterized by the following formula (B): melt flow ratio (I 21 / I 2 ) is less than (-36.9 * melt index (I 2 )) + 80.0 (EQ. (B)), where* Multiplication is indicated by ×, addition by +, and the symbol for "less than" is <; and (iii) a melt flow ratio of from 30 to 70 (I 21 / I 2 ). In some embodiments, the C4-uLLDPE is characterized by any one of the combinations of properties (iv) through (vii): (iv) melt flow ratio properties (i) and (ii); (v) melt flow ratio properties (i) and (iii); (vi) melt flow ratio properties (ii) and (iii); and (vii) each of the melt flow ratio properties (i) through (iii). The high load melt index (I 21 ) is measured according to ASTM D1238-13 using conditions of 190 °C / 21.6 kg, and the melt index (I 2 ) is measured according to ASTM D1238-13 using conditions of 190 °C / 2.16 kg. In some embodiments, the C4-uLLDPE has a melt flow ratio (I 21 / I 2 ) of from 35 to 64, alternatively from 35 to 40, alternatively from 50 to 62, alternatively from 51 to 55, alternatively from 57 to 63. For the avoidance of all doubt, "-36.9" is negative 36.9. In Formulas EQ.(A) and EQ.(B), an attempt is made to describe the C4-uLLDPE by separately depicting and further depicting its melt rheological property space, which is believed to be related to the enhanced processability of the C4-uLLDPE in the process of manufacturing films.
[0036] In some embodiments, the unimodal linear low density ethylene / 1-butene copolymer has a short chain branching distribution that is different from that of a reference unimodal linear low density ethylene / 1-hexene copolymer (reference EH copolymer, as defined herein), where the difference is designated δ(SCBD) and δ(SCBD) is greater than 3%. The difference is expressed as a percentage, and the EH reference copolymer meets the following requirements: (a) is synthesized using the same catalyst and cocatalyst and the same process and process conditions as those used to synthesize the C4-uLLDPE copolymer; (b) has a molecular weight distribution in which at least one molecular weight moment M w , M n or M z is within plus or minus (±) 8% of the same at least one molecular weight moment M w , M n or M z of the C4-uLLDPE copolymer, both measured by the GPC test method described herein in the same run queue; and (c) has a density within ±0.001 g / cm 3The density within both is measured by ASTM D792-13. This percentage difference in SCBD values between C4-uLLDPE and the reference EH copolymer is referred to as “δ(SCBD)” or “ΔSCBD” and is measured by compositional comonomer distribution analysis (iCCD) according to the δ(SCBD) test method described later. In some embodiments, δ(SCBD) is 5% or greater, alternatively 5% to 40%, alternatively 7% to 20%, alternatively 8% to 18%, alternatively 9.0% to 16.9%.
[0037] In some embodiments, C4-uLLDPE has a compositional distribution breadth index (CDBI) greater than (“>”) 70%, alternatively >75%, alternatively >80%, alternatively >85%, alternatively >92%, alternatively >95%, alternatively >97%; and wherein the CDBI is less than or equal to 100%. The CDBI is defined as the weight percentage of the polymer fraction having a comonomer content within plus or minus (“±”) 50 percentage (%) of the median comonomer content (as reported in WO 93 / 03093). The CDBI is calculated using the short chain branching distribution measured by the iCCD method and the comonomer composition correlation relative to the elution temperature as described later.
[0038] In some embodiments, C4-uLLDPE has an M of 20,000 grams per mole (g / mol) to 30,000 g / mol, alternatively 24,000 g / mol to 26,000 g / mol n . M is measured according to the high temperature GPC test method described later n .
[0039] In some embodiments, C4-uLLDPE has an M of 80,000 grams per mole (g / mol) to 120,000 g / mol, alternatively 88,000 g / mol to 112,000 g / mol w . M is measured according to the high temperature GPC test method described later w .
[0040] The C4-uLLDPE of the present invention can be prepared by copolymerizing ethylene and 1-butene under gas phase polymerization conditions such as those described in the later examples using a bridged bis(tetrahydroindenyl)zirconocene catalyst to prepare C4-uLLDPE. The bridged bis(tetrahydroindenyl)zirconocene catalyst is selected from the group consisting of: ethylenebis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, ethylenebis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl, dimethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, dimethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl, diphenylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, diphenylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl, diethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, and diethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl. The copolymerization is carried out in a gas phase polymerization reactor and under the gas phase polymerization conditions used in the UNIPOL TM PE process. The UNIPOL TM PE process has long been available from Univation Technologies LLC of Houston, Texas, USA, and is described in numerous existing patents ("UNIVATION"). UNIVATION is a wholly-owned subsidiary of The Dow Chemical Company ("DOW") of Midland, Michigan, USA.
[0041] The bridged bis(tetrahydroindenyl)zirconocene catalyst for preparing C4-uLLDPE is prepared by contacting a bridged bis(tetrahydroindenyl)zirconocene X 2 pre-catalyst with an activator (e.g., MAO), where X is a halogen, alkyl, or benzyl; alternatively chloride or methyl; alternatively chloride. The bridged bis(tetrahydroindenyl)zirconocene X 2 pre-catalyst is optionally selected from the group consisting of: ethylenebis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, ethylenebis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl, dimethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, dimethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl, diphenylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, diphenylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl, diethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, and diethylsilylbis(4,5,6,7-tetrahydroindenyl)zirconium dimethyl. See U.S. Patent No. US 8,957,159B2. In some embodiments, the bridged bis(tetrahydroindenyl)zirconocene catalyst is an XCAT selected from UNIVATION TMEZ-100 catalyst. After copolymerization and before any post-reactor blending, the post-reactor treatment step deactivates the catalyst such that the C4-uLLDPE is free of active catalyst and any other volatile organic compounds. The C4-uLLDPE may contain non-volatile residues of bridged bis(tetrahydroindenyl)zirconocene catalysts such as inactive Zr salts.
[0042] The C4-uLLDPE may be formulated with one or more additives for polyethylene articles such as, but not limited to, films. In some embodiments, the one or more additives include additives for films such as one or more antioxidants, one or more ultraviolet (UV) light stabilizers, one or more colorants, and / or one or more antimicrobial agents.
[0043] The C4-uLLDPE or formulation may be in the form of a melt at a temperature above 130 °C. Alternatively, the C4-uLLDPE or formulation may be in a solid form such as a powder, granule, or pellet.
[0044] The C4-uLLDPE or formulation may be used without any other polyolefin polymers. For example, the C4-uLLDPE or formulation may be free of each of low-density polyethylene, a reference linear low-density polyethylene different from the C4-uLLDPE of the present invention, high-density polyethylene, polypropylene, halogenated polyolefins, silicon-containing polyolefins, and polyolefin terpolymers.
[0045] Another embodiment is a post-reactor blend that comprises a unimodal linear low-density ethylene / 1-butene copolymer and a different polyolefin polymer.
[0046] The post-reactor blend may be prepared by a method that includes: melting a solid of the C4-uLLDPE to form a melt thereof; melting a solid of the different polyolefin polymer to form a melt thereof; and mixing the melts together to form the post-reactor blend. The mixing step may be carried out before (e.g., as pellets), during (as pellets / partial melt), or after (as melts) the melting step.
[0047] The C4-uLLDPE, formulation, or post-reactor blend has a balance between the processability characteristics required to prepare a blown film and the mechanical and abuse characteristics required for the blown film to withstand the forces and loads that a bulk packaging film experiences during transportation and storage. However, the blown film that contains C4-uLLDPE has increased directional tearability in the machine direction (MD), meaning that one can manually tear the film or package with their hands. This balance of properties is achieved by combining the combination of C4-uLLDPE properties described herein. This combination of properties is the result of preparing the C4-uLLDPE with a bridged bis(tetrahydroindenyl)zirconocene catalyst under gas-phase polymerization conditions.
[0048] The C4-uLLDPE and the post-reactor blend can be used to make fabricated articles. The fabricated articles are not limited to films or articles made from or containing films, such as food bags and packaging wraps. However, the C4-uLLDPE can be used to make films and articles made from or containing films, such as food bags and packaging wraps.
[0049] Another embodiment is a film that comprises a unimodal linear low density ethylene / 1-butene copolymer or a post-reactor blend.
[0050] In some embodiments, the film is a single-layer film consisting of one layer, and one of the layers comprises a unimodal linear low density ethylene / 1-butene copolymer or a post-reactor blend. In some embodiments, if the film has a thickness of 0.0254 mm (1 mil) and is prepared under the film-making conditions described in the examples, the film is characterized by at least one of the limitations (i) to (iii): (i) a yield stress CD of 11.7 megapascals (MPa) to 20.7 MPa; (ii) a strain at break CD (elongation at break CD) of 630% to 690%; and / or (iii) a strain at break CD (elongation at break MD) of 510% to 530%. In some embodiments, the oriented tearability of the film is characterized in that: for a single-layer embodiment of a film having a thickness of 0.0254 millimeters formed according to the film-forming procedure of any one of Examples 1 to 3 of the present invention described later, the Elmendorf tear CD and the Elmendorf tear MD are measured according to the film test method for Elmendorf multi-anti-tearability described later, wherein the single-layer film has an Elmendorf tear MD of 15 grams force (gf) to 100 gf, alternatively 15 gf to 30 gf, alternatively 21 gf to 99 gf; and optionally an Elmendorf tear ratio CD / MD of 6.1 to 13, alternatively 6.2 to 7.2, alternatively 11.5 to 12.5.
[0051] In other embodiments, the film is a multi-layer film consisting of 3 to 12 layers, wherein at least one of the 3 to 12 layers comprises a unimodal linear low density ethylene / 1-butene copolymer or a post-reactor blend.
[0052] The multilayer film can be composed of 3 to 12 layers, including 2 to 4 outer layers and 1 to 8 core layers; at least one outer layer independently contains 10 wt% to 100 wt%, alternatively 70 wt% to 100 wt% of C4-uLLDPE and 90 wt% to 0 wt%, alternatively 30 wt% to 0 wt% of other polyolefin polymers, all based on the total weight of C4-uLLDPE + other polyolefin polymers in at least one outer layer; and at least one core layer independently contains 80 wt% to 100 wt% of C4-uLLDPE and 20 wt% to 0 wt% of other polyolefin polymers, all based on the total weight of C4-uLLDPE + other polyolefin polymers in at least one core layer.
[0053] Another embodiment is a method for preparing a film, which includes extruding at least one melt of a unimodal linear low density ethylene / 1-butene copolymer or a post-reactor blend as a film having at least one layer. In some embodiments, the film is a single-layer film, and the method includes: melt-extruding a melt containing a unimodal linear low density ethylene / 1-butene copolymer or a post-reactor blend through a single die orifice to prepare a single-layer film. Figure 1 An embodiment of a mostly rolled-up single-layer film is shown.
[0054] In other embodiments, the film is a multilayer film, and the method includes: melt-extruding at least one melt containing a unimodal linear low density ethylene / 1-butene copolymer or a post-reactor blend through different die orifices among 3 to 12 die orifices, and optionally extruding a melt containing a unimodal linear low density ethylene / 1-butene copolymer, low density polyethylene, unimodal linear low density ethylene / 1-hexene copolymer or their post-reactor blends through a different one of the die orifices to prepare a multilayer film composed of 3 to 12 layers. Figure 3 and 4 Embodiments of multilayer films are illustrated in.
[0055] In the embodiment of a multilayer film laminate, the method includes: melting one or more embodiments of C4-uLLDPE, formulations or post-reactor blends and optionally a single C4-uLLDPE to obtain one or more of their melts; and extruding the melt through a separate extruder configured to form a multilayer film laminate. The Alpine 7 film production line can be used for this process, where the multilayer film laminate is composed of 3 layers as shown in Figure 3 or 7 layers as shown in Figure 4 shown.
[0056] In a blown film embodiment, the method comprises: melting a C4-uLLDPE or a post-reactor blend to obtain its melt; extruding the melt through a die configured to form a bubble to prepare a bubble of the LLDPE copolymer; and blow molding (inflating) the bubble using a blown film machine to thereby prepare a blown film. The C4-uLLDPE, formulation or post-reactor blend has a balance between the processability characteristics required to prepare a blown film and the mechanical and abuse characteristics required for the blown film to withstand the forces and loads that a bulk packaging film is subjected to during transportation and storage.
[0057] Film preparation methods are well known. See, for example, LyondellBasell, "A Guide to Polyolefin Film Extrusion", Publication 6047 / 1004 (available from lyb.com) and Qenos Pty, Ltd., "Film Extrusion and Conversion - Technical Guide" (July 2015) (available from qenos.com).
[0058] A film comprising the above C4-uLLDPE, formulation or post-reactor blend. The film is particularly useful for packaging applications, such as food packaging made by standard film blowing methods and equipment.
[0059] Some embodiments of the film consist of a single layer ("single layer film"), wherein the single layer consists of a C4-uLLDPE, formulation or post-reactor blend. Figure 1 A roll of single layer film is shown, which has been partially unrolled (or not fully rolled up), wherein the vertical arrows illustrate the machine direction (MD) and the cross direction (CD). The improvement in the oriented tearing of the single layer film of the present invention means that the single layer film can be torn more easily in the machine direction (MD) or against the machine direction (against MD) than in the cross direction (CD), as the case may be. In addition, the MD and anti-MD tear resistance of the single layer film of the present invention are increased relative to the MD and anti-MD tear resistance of a comparative single layer film. The comparative single layer film is a film having the same thickness and prepared from a comparative linear low density ethylene / 1-hexene copolymer ("C6-uLLDPE") under the same film manufacturing conditions, the linear low density ethylene / 1-hexene copolymer being prepared by copolymerizing ethylene / 1-hexene using the same bis(tetrahydroindenyl)zirconocene catalyst, and wherein the comparative C6-uLLDPE has a density substantially the same as the density of the C4-uLLDPE of the present invention, i.e., their densities are within ±0.002 g / cm 3 preferably ±0.001 g / cm 3inside; and wherein the comparative C6-uLLDPE has a melt flow ratio (I 21 / I 2 ) that is substantially the same as the melt flow ratio (I 21 / I 2 ) of the C4-uLLDPE of the present invention, i.e., their I 21 / I 2 values are within ±1.4, preferably ±1.1 of each other.
[0060] Other embodiments of the film consist of two or more layers ("multilayer film"), wherein at least one of the two or more layers consists of the C4-uLLDPE, formulation, or post-reactor blend of the present invention, and each of the other layers of the two or more layers independently consists of a polyolefin composition selected from polypropylene, low density polyethylene (LDPE), single-site linear low density polyethylene (LLDPE), high density polyethylene (HDPE), the C4-uLLDPE, formulation, or post-reactor blend of the present invention, or any combination of two or more of such polyolefin compositions. In some embodiments, at least two of the two or more layers independently consist of the C4-uLLDPE, formulation, or post-reactor blend of the present invention.
[0061] Some embodiments of the multilayer film can consist of 3 to 12 layers, alternatively 5 to 12 layers, alternatively 6 to 12 layers, alternatively 7 layers, wherein at least one of the above layers consists of C4-uLLDPE, formulation, or post-reactor blend. In some such embodiments, the polyolefin compositions of any two or more consecutive layers are different. In other embodiments, the polyolefin compositions of two or more consecutive layers are the same, and this is referred to herein as "similar layer grouping".
[0062] In some embodiments, the film consists of 3 or more layers, wherein at least one of the 3 or more layers is a core layer (inner layer) composed of low density polyethylene (LDPE), and at least two of the 3 or more layers "sandwich" the core layer and independently consist of the same or different C4-uLLDPE, formulation, or post-reactor blend.
[0063] Embodiments of the multilayer film comprising 3 layers consist of Figure 3The three-layer film 10 is illustrated in. The three-layer film 10 includes a first outer layer (epidermal layer or top layer) 20; a core layer (intermediate layer) 30; and a second outer layer (epidermal layer or bottom layer) 40. The core layer 30 is disposed between the top layer 20 and the bottom layer 40, i.e., the two layers 20 and 40 sandwich the core layer 30 therebetween. The top layer 20, the core layer 30, and the bottom layer 40 are contacted and bonded together to form the three-layer film 10. The term "core layer" refers to any inner layer in the multi-layer film; and the phrase "epidermal layer" refers to the outermost layer of the multi-layer film.
[0064] Each of the layers 20, 30, and 40 of the multi-layer film 10 in Figure 3 is made into a different single layer. Figure 3 Such a three-layer film 10 in is made by a film-forming process in which three different layers are arranged and combined in the following order: 20 / 30 / 40. All the layers can be prepared simultaneously or sequentially or any combination thereof. The reference numerals 21, 32, and 41 in Figure 3 are simply used to indicate that the layers 20, 30, and 40 are made into different single layers (whether simultaneously or sequentially) in the film-forming process. However, since the layers 20, 30, and 40 (21, 31, and 41) are prepared from the melt of a polyethylene composition, these layers can undergo some interfacial mixing such that in the final form, the cross-section of the three-layer film 10 can appear to have fewer than three layers in total.
[0065] In other embodiments, Figure 3 the three-layer film 10 in is part of a larger multi-layer film having a total of 4 to 12 layers (including a total of 4 or more layers). The layers 20, 30, and 40 can include any three consecutive layers of a multi-layer film having a total of 4 to 12 layers. In some such embodiments, the layer 20 of the three-layer film 10 is an outer layer or top layer, and the layers 30 and 40 are core layers or inner layers of a multi-layer film having a total of 4 to 12 layers. In other embodiments, each of the layers 20, 30, and 40 is a core layer or inner layer of a multi-layer film having a total of 4 to 12 layers.
[0066] In other embodiments, the multi-layer film has a total of 4 to 12 layers. One embodiment thereof is illustrated in Figure 4 the seven-layer film 100 in.
[0067] In Figure 4In it, the similar layer group 200 is composed of similar outer layers 21 and 22; the similar layer group 300 is composed of similar core layers 31, 32, and 33; and the similar layer group 400 is composed of similar outer layers 41 and 42. Layers 21 and 42 are the outermost layers respectively, and layers 22 and 41 are the outer layers adjacent to the outermost layers 21 and 42 respectively. The outer layer 22 is disposed between the outermost layer 21 and the core layer 31. The outer layer 41 is disposed between the outermost layer 42 and the core layer 33. The core layer 32 is disposed between the core layers 31 and 33. In some embodiments, the core layers 31, 32, and 33 are independently composed of LLDPE that is not part of the C4-uLLDPE, formulation, or post-reactor blend of the present invention, and the outer layers 21, 22, 41, and 42 are independently composed of the same or different C4-uLLDPE, formulation, or post-reactor blend of the present invention.
[0068] Figure 4 The 7-layer film 100 in it is made by a film-forming process of arranging and combining 7 different layers in the following order: 21 / 22 / 31 / 32 / 33 / 41 / 42. This can be carried out by a 7-layer film production line (such as an Alpine 7-layer film extruder).
[0069] In some embodiments of the multilayer film (e.g., Figure 2 and Figure 3 the multilayer films 10 and 100), at least one, alternatively each outer layer (e.g., layer 20 and 40 in the case of Figure 3 or layer 21, 22, 41, and 42 in the case of Figure 4 independently contains 10 wt% to 100 wt% of C4-uLLDPE and 90 wt% to 0 wt% of C6-uLLDPE, alternatively 10 wt% to 60 wt% of C4-uLLDPE and 90 wt% to 40 wt% of C6-Ulldpe, alternatively 20 wt% to 50 wt% of C4-uLLDPE and 80 wt% to 50 wt% of C6-Ulldpe, alternatively 20 wt% to 40 wt% of C4-uLLDPE and 80 wt% to 60 wt% of C6-Ulldpe, all based on the total weight of C4-uLLDPE + C6-uLLDPE in the outer layer. In some embodiments of the multilayer film (e.g., Figure 2 and Figure 3 the multilayer films 10 and 100), at least one, alternatively each outer layer (e.g., layer 20 and 40 in the case of Figure 3 or layer 21, 22, 41, and 42 in the case of Figure 4In the case of layers 21, 22, 41, and 42), they independently contain 70% to 98% by weight of C4-uLLDPE and 30% to 2% by weight of C6-uLLDPE, alternatively 80% to 97% by weight of C4-uLLDPE and 20% to 3% by weight of C6-uLLDPE, alternatively 86% to 94% by weight of C4-uLLDPE and 14% to 6% by weight of C6-uLLDPE, alternatively 90% by weight of C4-uLLDPE and 10% by weight of C6-uLLDPE, all based on the total weight of C4-uLLDPE + C6-uLLDPE in the outer layer.
[0070] In the case of a multilayer film (e.g., Figure 2 and Figure 3 In some embodiments of the multilayer films 10 and 100), at least one, alternatively each, core layer (e.g., in the case of Figure 3 is the intermediate layer 30 or in the case of Figure 4 is one or more of the core layers 31, 32, and 33) contains 80% to 100% by weight of C4-uLLDPE and 20% to 0% by weight of C6-uLLDPE, alternatively 85% to 100% by weight of C4-uLLDPE and 15% to 0% by weight of C6-uLLDPE, alternatively 95% to 100% by weight of C4-uLLDPE and 5% to 0% by weight of C6-uLLDPE, alternatively 100% by weight of C4-uLLDPE and 0% by weight of C6-uLLDPE, all based on the total weight of C4-uLLDPE + C6-uLLDPE in the core layer.
[0071] In the case of a multilayer film (e.g., Figure 2 and Figure 3 In some embodiments of the multilayer films 10 and 100), at least one, alternatively each, core layer (e.g., in the case of Figure 3 is the intermediate layer 30 or in the case of Figure 4in the case where one or more of the core layers 31, 32, and 33) contain 20 wt% to 100 wt% of C4-uLLDPE and 80 wt% to 0 wt% of C6-uLLDPE and / or HDPE, alternatively 30 wt% to 60 wt% of C4-uLLDPE and 70 wt% to 40 wt% of C6-uLLDPE and / or HDPE, alternatively 30 wt% to 50 wt% of C4-uLLDPE and 70 wt% to 50 wt% of C6-uLLDPE and / or HDPE, alternatively 40 wt% of C4-uLLDPE and 60 wt% of C6-uLLDPE and / or HDPE, all based on the total weight of C4-uLLDPE + C6-uLLDPE and / or HDPE in the core layer. Based on the total weight of C6-uLLDPE and HDPE, the total weight % of C6-uLLDPE and / or HDPE can be 100 wt% to 0 wt% of C6-uLLDPE and 0 wt% to 100 wt% of HDPE. In some embodiments, at least one layer of the film further comprises a polyolefin composition that is not part of the C4-uLLDPE, formulation, or post-reactor blend of the present invention. Examples are reference LLDPE, low density polyethylene (LDPE), or high density polyethylene (HDPE). In some embodiments, Figure 3 the core layer 30 of the 3-layer film 10 in Figure 4 or the core layers 31, 32, and 33 of the 7-layer film 100 in Figure 3 are composed of a reference LLDPE that is not C4-uLLDPE or C6-uLLDPE, and Figure 4 the layers 20 and 40 in
[0072] and the layers 21, 22, 41, and 42 in
[0073] are independently composed of the same or different C4-uLLDPE, formulation, or post-reactor blend of the present invention.
[0074] The blown film machine can be configured with a hopper in fluid communication with an extruder, the extruder being in heating communication with a heating device capable of heating polyethylene in the extruder to a temperature of up to 500 °C (e.g., 430 °C), and wherein the extruder is in fluid communication with a die having an inner diameter of 20.3 cm (8 inches) and a fixed die gap (e.g., a gap of 1.778 mm (70 mils)), a blow-up ratio of 2.5:1, and a frost line height (FLH) of 76 cm ± 10 cm (30 inches ± 4 inches) from the die. Step (a) can be carried out in the hopper. Steps (b) and (c) can be carried out in the extruder and at a temperature of 400 °C to 450 °C (e.g., 430 °C). Step (d) can be carried out in the die and after leaving the die. The machine can have the capacity for the feed rate of (A) and (B) and the production rate of the film (50 kg / hour to 200 kg / hour, e.g., 91 kg (201 lbs) / hour at 430 °C).
[0075] The film can be used to prepare containers and wrappings having at least one enhanced optical property. Examples of such containers are bags, such as ice bags and grocery bags. Examples of such wrappings are stretch films, meat wrappings, and food wrappings.
[0076] The film description focuses on packaging applications, but the applications of C4-uLLDPE, formulations, or post-reactor blends are not limited to packaging films or even films in general. The available applications of C4-uLLDPE, formulations, or post-reactor blends also include various non-film products, such as automotive parts.
[0077] In some embodiments, the film is a single-layer film comprising C4-uLLDPE and no other polyolefin polymers, and wherein the film is characterized by any one or more of the following properties: Elmendorf tear in the machine direction (“Elmendorf tear MD”) and Elmendorf tear in the cross (transverse) direction (“Elmendorf tear CD”) measured by the film test method for Elmendorf multi-rip resistance; dart impact measured by the film test method for dart impact resistance described later; gloss at 45° measured by the film test method for gloss described later; haze measured by the film test method for haze described later; secant modulus at 1% MD and secant modulus at 1% CD measured by the film test method for 1% secant modulus described later; yield stress CD and yield stress MD measured by the yield stress test method described later; yield strain MD and yield strain CD measured by the yield strain test method described later; fracture stress MD and fracture stress CD measured by the fracture stress test method described later; and fracture strain MD (also referred to as elongation at break MD) and fracture strain CD (also referred to as elongation at break CD) measured by the fracture strain test method described later. Of particular interest in characterizing the oriented tear resistance of the films of the present invention are the Elmendorf tear MD and the Elmendorf tear CD / MD ratio. Of particular interest in characterizing the overall toughness of the films of the present invention are the following properties: dart impact and the MD and CD properties of the 1% secant modulus, yield stress, yield strain, fracture stress, and fracture strain. Of particular interest in characterizing the optical properties of the films of the present invention are the gloss at 45° and the haze. For purposes of characterization and comparison, any film thickness can be used to generate data for the foregoing film properties. In some embodiments, the film thickness is 1 mil (0.025 millimeters (mm)).
[0078] A manufactured article that includes an object and a film covering the object and has directional tearability and includes a unimodal linear low density ethylene / 1-butene copolymer. The object can be any object that needs to be covered. Examples include food (e.g., the manufactured article is packaged food), boxes (e.g., the manufactured article is a set of boxes that are wrapped), and electronic items (e.g., the manufactured article is an electronic display or computer component that is wrapped). In some embodiments, the directional tearability of the film is characterized by: a single layer embodiment of a film having a thickness of 0.0254 millimeters formed according to the film forming procedure of any one of Embodiments 1 to 3 of the present invention described later, measuring Elmendorf tear CD and Elmendorf tear MD according to the film test method for Elmendorf multi-tear resistance described later, wherein the single layer film has an Elmendorf tear MD of 15 grams force (gf) to 100 gf, alternatively 15 gf to 30 gf, alternatively 21 gf to 99 gf; and optionally an Elmendorf tear ratio CD / MD of 6.1 to 13, alternatively 6.2 to 7.2, alternatively 11.5 to 12.5.
[0079] Preparation method: According to ASTM D4703-10, "Standard Practice for Compression Molding Thermoplastic Materials into Test Specimens, Plaques, or Sheets", prepare test specimens, test substrates, or test sheets.
[0080] Density test method: Measure according to ASTM D792-13, "Standard Test Methods for Density and Specific Gravity (Relative Density) of Plastics by Displacement, Method B" (for testing solid plastics in liquids other than water, such as in the liquid 2-propanol). Report the results in grams per cubic centimeter (g / cm 3 )
[0081] Melt index ("I 2 ") test method: For vinyl (co)polymers, measure according to ASTM D1238-13 using the conditions of 190 °C / 2.16 kg (previously known as "Condition E").
[0082] The molecular weights Mw (weight average), Mn (number average), and Mz (z average) are measured according to the high-temperature gel permeation chromatography (GPC) test method described below.
[0083] High-temperature gel permeation chromatography (GPC) test method: Performed on samples to determine the molecular weight distribution (MWD) of the samples and the corresponding moments (Mn, Mw, and Mz) of the samples. The chromatographic system used for measuring GPC includes a Polymer Char GPC-IR high-temperature GPC chromatograph (available from Polymer Char, Valencia, Spain), which is equipped with a 4-capillary differential viscometer detector and an IR5 multi-fixed wavelength infrared detector (available from Polymer Char). A Precision Detectors 2-angle laser light scattering detector model 2040 (available from Precision Detector, currently Agilent Technologies) is added to the chromatographic system. The 15-degree angle of the light scattering detector is used for calculation purposes. Data collection and data processing are performed using GPC One software (available from Polymer Char). The system is equipped with an on-line solvent degassing device (available from Agilent Technologies).
[0084] Both the detector chamber and the column chamber of the chromatograph are operated at 150 °C. The columns used are 4 PLgel Mixed A 7.5 mm x 300 mm 20-micron columns (Agilent Technologies). The chromatographic solvent used is distilled 1,2,4-trichlorobenzene (TCB) containing 200 ppm butylated hydroxytoluene (BHT). The solvent source is nitrogen sparged. The injection volume for each sample in the sample is 200 μL, and the flow rate is 1.0 mL / min. In other words, the samples are prepared semi-automatically using Polymer Char "Instrument Control" software, where the samples are targeted at a weight of 2 mg / mL, and the solvent (containing 200 ppm BHT) is added to vials covered with pre-nitrogen bubbled septa via a Polymer Char high-temperature autosampler. The samples are dissolved at 160 °C for 2 hours with "low-speed" shaking.
[0085] For conventional molecular weight measurements, the GPC column set was calibrated with 21 narrow molecular weight distribution polystyrene standards having molecular weights in the range of 580 to 8,400,000 (available from Polymer Laboratories, now Varian) and arranged in 6 “cocktail” mixtures. For molecular weights ≥ 1,000,000, the polystyrene standards were prepared at 0.025 g in 50 mL of solvent, and for molecular weights < 1,000,000, the polystyrene standards were prepared at 0.05 g in 50 mL of solvent. The polystyrene standards were dissolved at 80 °C with gentle stirring for 30 minutes. The narrow standard mixtures were run first and in descending order starting from the highest molecular weight component to minimize degradation of the standards. The peak molecular weight of the polystyrene standards was converted to polyethylene molecular weight using the following formula (I): M 聚乙烯 = A*(M 聚苯乙烯 )^B Formula (I) , where in formula (I), “M” is the molecular weight of polystyrene or polyethylene; the value of “A” is 0.417; and the value of “B” equals 1.000. A third-order polynomial was used to fit the corresponding polystyrene calibration points.
[0086] iCCD test method: “iCCD” is an improved method for the analysis of comonomer content distribution (CCD); and is based on the method described in WO2017040127A1. The test method was carried out using a crystallization elution fractionation (CEF) instrument (available from PolymerChar) equipped with an IR-5 detector and a dual-angle precision detector light scattering detector model 2040 (available from Agilent Technologies). o-Dichlorobenzene (ODCB, 99% anhydrous grade or technical grade) was used as the solvent. Silica gel 40 (with a particle size of 0.2 mm to about 0.5 mm; available from EMD Chemicals) could be used to dry the ODCB solvent. The dried silica was packed into three empty and cleared HT-GPC columns (with dimensions of 300 mm x 7.5 mm (ID)) to further purify the ODCB solvent as the eluent. The CEF instrument was equipped with an autosampler having a nitrogen (N 2 ) purge function. The ODCB was bubbled with dried N 2 for 1 hour before use.
[0087] Samples were prepared by shaking at 160 °C for 1 hour using an autosampler at 4 mg / mL (unless otherwise specified). The injection volume of the sample was 300 microliters (μL). The temperature profile of the iCCD was as follows: crystallization from 105 °C to 30 °C at 3 °C / min; thermal equilibrium at 30 °C for 2 minutes (including the elution time of the soluble fraction set to 2 minutes); elution from 30 °C to 140 °C at 3 °C / min. The flow rate of the sample during crystallization was 0.0 mL / min. The flow rate of the sample during elution was 0.50 mL / min. Data were collected at a rate of one data point per second.
[0088] The iCCD column used was a 15 cm (length) x 1 / 4 inner diameter (ID) stainless steel tube packed with gold-coated nickel particles (Bright 7GNM8-NiS; available from Nippon Chemical Industrial Co.). Column packing and conditioning were performed using the slurry method according to the method described in WO2017040127A1. The final pressure for trichlorobenzene (TCB) slurry packing was 150 bar (10 MPa).
[0089] Column temperature calibration was performed using a mixture of the following: (i) 1.0 mg / mL monodisperse linear homopolymer polyethylene (copolymer content zero, melt index (I 2 ) of 1.0 g / cm 3 and polydispersity (M w / M n ) of approximately 2.6 as measured by the GPC test method described above) as the "reference material"; mixed with 0.5 mg / mL eicosane in ODCB (Cong et al., J. Chromatography A, 1662 (2022) 462724). iCCD temperature calibration consisted of the following four steps: (1) calculating the delay volume defined as the temperature offset between the measured peak elution temperature of eicosane minus 30.00 °C; (2) subtracting the temperature offset of the elution temperature from the iCCD raw temperature data (note that this temperature offset is a function of experimental conditions such as elution temperature, elution flow rate, etc.); (3) creating a monodisperse linear calibration line that converts the elution temperature in the range of 30.00 °C to 140.00 °C such that the monodisperse linear homopolymer polyethylene reference material has a peak temperature of 101.0 °C and eicosane has a peak temperature of 30.0 °C; (4) for the soluble fraction measured isothermally at 30 °C, linearly extrapolating the elution temperature below 30.0 °C using the method described in U.S. Patent No. 9,688,795 at an elution heating rate of 3 °C / min. Using GPCOne software (available from PolymerChar) to generate the SCBD distribution curve dWi / dT, where Wi is T i the mass at, where T i is the calibrated elution temperature.
[0090] The comonomer content versus the elution temperature of the iCCD was constructed using solution methods with 12 reference materials (ethylene homopolymers and ethylene-octene random copolymers prepared with a single-site metallocene catalyst having an ethylene equivalent weight average molecular weight in the range of 35,000 to 128,000). All of these reference materials were analyzed in the same manner as previously specified at 4 mg / mL. The correlation between the comonomer mole fraction and the elution temperature (T in degrees Celsius) follows the expression: ln(1 - comonomer mole fraction) = -208.328 / (elution temperature + 273.12) + 0.55846.
[0091] The compositional distribution breadth index (CDBI) is defined as the weight percentage of polymer molecules having a comonomer content within + / - 50% of the median total molar comonomer content (as reported in WO 93 / 03093). The CDBI of polyolefins can be conveniently calculated from SCBD data obtained by techniques known in the art, such as, for example, temperature rising elution fractionation ("TREF"), such as the temperature rising elution fractionation described in the following: Wild et al., Journal of Polymer Science, Poly. Phys. Ed., Vol. 20, 441 (1982); L.D. Cady, "The Role of Comonomer Type and Distribution in LLDPE Product Performance", SPE Regional Technical Conference, Quaker Square Hilton, Akron, OH, 107-119 (October 1-2, 1985); and U.S. Patent Nos. 4,798,081 and 5,008,204.
[0092] In the present case, the iCCD CDBI is accordingly calculated using the short chain branching distribution measured by the iCCD method and the comonomer composition correlation as described above with respect to the elution temperature.
[0093] δ(SCBD) Test Method: Used in this article to calculate the percentage difference between the short-chain branching distribution of the single-peak linear low-density ethylene / 1-butene copolymer ("C4-uLLDPE copolymer") of the present invention and the short-chain branching distribution (SCBD) of the reference single-peak linear low-density ethylene / 1-hexene copolymer ("EH reference copolymer"). To determine δ(SCBD), the EH reference copolymer meets the following requirements: (a) synthesized using the same catalyst and cocatalyst as used for synthesizing the C4-uLLDPE copolymer, as well as the same process and process conditions; (b) having a molecular weight distribution, where at least one molecular weight moment M w 、M n or M z is within plus or minus (±) 8% of the same at least one molecular weight moment M w 、M n or M z of the C4-uLLDPE copolymer, both measured by the GPC test method described in the same run queue in this article; and (c) having a density within ±0.001 g / cm 3 of the density of the C4-uLLDPE copolymer, both measured by ASTM D792-13. The δ(SCBD) test method is carried out according to the following procedure: (1) Analyze the EH reference copolymer and the C4-uLLDPE copolymer sequentially in the same run queue of the iCCD analysis according to the iCCD method described elsewhere in this article to generate iCCD data for both copolymers; (2) Process the iCCD data of the EH reference copolymer and the iCCD data of the C4-uLLDPE copolymer as described above; (3) Using the following mathematical formula, generate a cumulative distribution for each data point with a fixed temperature step of 0.1 °C for the entire range of iCCD integration: (4) Plot the cumulative distribution against the elution temperature for each of the EH reference copolymer and the C4-uLLDPE copolymer; (5) Find the elution temperature ("T15") of the EH reference copolymer corresponding to the cumulative distribution at 15.0%; (6) Find the elution temperature ("T75") of the EH reference copolymer corresponding to the cumulative distribution at 75.0%; (7) From the cumulative distribution curve of the C4-uLLDPE copolymer, obtain the corresponding cumulative weight %, dW / dT(T15), and dW / dT(T75) at the elution temperatures of T15 and T75 respectively; (8) According to the following mathematical formula: Calculate δ(SCBD) as the sum of the differences between the SCBD of the EH reference copolymer and the SCBD of the C4-uLLDPE copolymer, where δ(SCBD) is expressed as a percentage difference.
[0094] Long-chain branching (LCB) value test method: The amount of LCB present in the EB LLDPE resin can be measured using a combination of nuclear magnetic resonance (NMR) techniques described in the following literature: Z. Zhou, S. Pesek, J. Klosin, M. Rosen, S. Mukhopadhyay, R. Cong, D. Baugh, B. Winniford, H. Brown, K. Xu, “Long chain branching detection and quantification in LDPE with special solvents, polarization transfer techniques, and inverse gated 13 13C NMR spectroscopy”, Macromolecules, 2018, 51, 8443; Z. Zhou, C. Anklin, R. Cong, X. Qiu, R. Kuemmerle, “Long-chain branch detection and quantification in ethylene-hexene LLDPE with 13 13C NMR”, Macromolecule, 2021, 54, 757; and Z. Zhou, C. Anklin, R. Kuemmerle, R. Cong, X. Qiu, J. DeCesare, M. Kapur, R. Patel, “Very sensitive 13 13C NMR method for the detection and quantification of long-chain branches in ethylene-hexene LLDPE”, Macromolecule, 2021, 54, 5985. The chemical shift range for LCB calculation is between 38.12 ppm and 38.22 ppm.
[0095] Film test method for transparency: The optical property transparency is measured according to ASTM D1746-15, Standard Test Method for Transparency of Plastic Sheeting. The transparency is measured using a BYK-Gardner Haze-Gard Plus. The transparency is expressed as the percentage of the intensity of light with and without the sample in the light path.
[0096] Film test method for anti-dart impact resistance: Measured according to ASTM D1709-16 "Standard Test Methods for Impact Resistance of Plastic Film by the Free-Falling Dart Method".
[0097] Film test method for Elmendorf multi-tear resistance: Measured in the transverse direction (CD) and longitudinal direction (MD) according to ASTM D1922-15(2020) "Standard Test Method for Propagation Tear Resistance of Plastic Film and Thin Sheeting by Pendulum Method".
[0098] Film test method for puncture resistance: Measured according to ASTM D5748–95(2012) "Standard Test Method for Protrusion Puncture Resistance of Stretch Wrap Film". The puncture resistance of the film is determined as the film's resistance to penetration by impacting the film with a probe at a standard speed (such as 250 millimeters per minute (mm / min)). The probe is coated with polytetrafluoroethylene and has an outer diameter of 1.905 cm (0.75 inches). The film is clamped during the test. The probe finally penetrates or damages the clamped film. The mechanical test software is used to record the peak fracture force, i.e., the maximum force, energy (work), and the damage distance when the probe penetrates, which are used to break or penetrate the clamped film. The probe applies biaxial stress to the clamped film, and this biaxial stress represents the type of stress that the film encounters in many end-use applications. This resistance is a measure of the film's energy absorption capacity to resist puncture under these conditions.
[0099] Film test method for glossiness: Measure the optical glossiness according to ASTM D2457-13 "Standard Test Method for Specular Gloss of Plastic Films and Solid Plastics". The specular glossiness is measured using a glass gauge at an incident angle of 45°. The specular glossiness has no unit.
[0100] Film test method for haze: Measure the optical haze according to ASTM D1003-13, "Standard Test Method for Haze and Luminous Transmittance of Transparent Plastic". Measure the haze using a haze meter. Express the haze as the percentage of light transmission that deviates from the incident light beam due to forward scattering when passing through the film.
[0101] Film test method for hot tack: Measure according to ASTM F-1921 (Method B) using an Enepay commercial testing machine. Before testing, condition the sample at 23 °C and 50% relative humidity (R.H.) for at least 40 hours. The hot tack test simulates filling a pouch or bag with material before the seal has had a chance to fully cool. Cut a sheet with dimensions 8.5 inches x 14 inches from the film, with the longest dimension being longitudinal. Cut a strip 1” wide and 14” long from the film [the sample only needs to have a length sufficient for clamping]. Test these samples over a range of temperatures and report the results as the maximum load as a function of temperature. A typical temperature step is 10 °C, with 6 replicates at each temperature. The following are typical parameters used in the test: Sample width: 25.4 millimeters (mm, 1.0 inch); Seal pressure: 0.275 Newton per square millimeter (N / mm 2 ); Seal dwell time: 1.0 second (sec); Peel speed: 200 millimeters per second (mm / sec); Seal depth = 12.7 mm (0.5 inch). Report the data as a hot tack curve, where the average hot tack force is plotted as a function of temperature in Newton (N).
[0102] Film test method for 1% secant modulus: Measure in the transverse (CD) and longitudinal (MD) directions according to ASTM D882-12, "Standard Test Methods for Tensile Properties of Thin Plastic Sheeting". Use the 1% secant modulus in the transverse (CD) or longitudinal (MD) direction. Report the results in megapascals (MPa). 1,000.0 pounds per square inch (psi) = 6.8948 MPa.
[0103] Film Test Method for Zebedee Transparency: Measure the optical Zebedee transparency according to ASTM D1746-15, Standard Test Method for Transparency of Plastic Sheeting. Measure the transparency using a Zebedee CL-100 meter. Express the Zebedee transparency as the percentage of the intensity of light with and without the sample in the light path.
[0104] Yield Stress Test Method: Measure in the cross direction (CD) and the machine direction (MD) according to ASTM D882-12, Standard Test Method for Tensile Properties of Thin Plastic Sheeting.
[0105] Yield Strain Test Method: Measure in the cross direction (CD) and the machine direction (MD) according to ASTM D882-12.
[0106] Breaking Stress Test Method: Measure in the cross direction (CD) and the machine direction (MD) according to ASTM D882-12.
[0107] Breaking Strain Test Method: Measure in the cross direction (CD) and the machine direction (MD) according to ASTM D882-12.
[0108] Example
[0109] Gas Phase Polymerization Process: In a fluidized bed gas phase polymerization (FB-GPP) reactor with a distribution grid, use XCAT TM EZ-100 (a commercial bridged bis(tetrahydroindenyl)zirconocene catalyst) to polymerize ethylene and comonomers (C x , 1-butene (C x =C 4 ) or 1-hexene (C x =C 6)) Copolymerize to separately prepare a single-peak linear low-density ethylene / 1-butene copolymer or a single-peak linear low-density ethylene / 1-hexene copolymer. The FB-GPP reactor has an inner diameter of 0.35 meters (m) and a bed height of 2.3 m, and the fluidized bed is composed of polymer particles. The flowing fluidizing gas passes through a recycle gas circuit that sequentially includes a recycle gas compressor and a shell-and-tube heat exchanger having a water side and a gas side. The fluidizing gas flows through the compressor, then the water side of the shell-and-tube heat exchanger, and then enters the FB-GPP reactor below the distribution grid. The fluidizing gas velocity is listed in Table 1 below. The fluidizing gas then exits the FB-GPP reactor through nozzles in the top of the reactor and is continuously recycled through the recycle gas circuit. A constant fluidized bed temperature listed in Table 1 below is maintained by continuously adjusting the temperature of the water on the shell side of the shell-and-tube heat exchanger. A feed stream of ethylene, nitrogen, and hydrogen together with the comonomer is introduced into the recycle gas line. The FB-GPP reactor is operated at the total pressure shown in Table 1 below, and the reactor gas is discharged to a combustion tower to control the total pressure. The individual flow rates of ethylene, nitrogen, hydrogen, and comonomer (C x ) are adjusted to maintain their respective gas composition targets. The ethylene partial pressure, C x / C 2 molar ratio, and H 2 / C 2 molar ratio are set to the values shown in Table 1 below. The isopentane (iC 5 ) concentration is maintained at the value shown in Table 1 below. Isopentane is used as an induced condensation agent (ICA). The average residence time of the copolymer is shown in Table 1 below. The concentration of all gases is measured using on-line gas chromatography. The fluidized bed is maintained at a constant height by withdrawing a portion of the fluidized bed at a rate equal to the rate of formation of the particulate product single-peak LLDPE. The product is removed semi-continuously through a series of valves into a fixed-volume chamber. Nitrogen purging removes a substantial portion of the entrained and dissolved hydrocarbons in the fixed-volume chamber. After purging, the product is discharged from the fixed-volume chamber into a fiber pack for collection. The product is further treated with a small stream of moist nitrogen to deactivate any trace amounts of residual catalyst and cocatalyst. The rate of catalyst feed is set to maintain the productivity value of the single-peak LLDPE product shown in Table 1 below.
[0110] Table 1: Polymerization conditions for preparing the inventive C4-uLLDPE of Examples 1 to 3 of the present invention and comparative C6-uLLDPE of Comparative Examples A to C of the present invention.
[0111] Polymerization conditions CE A CE B CE C IE1 IE2 IE3 <![CDATA[XCAT TM EZ-100 catalyst]]> Yes Yes Yes Yes Yes Yes Monomer used Ethylene Ethylene Ethylene Ethylene Ethylene Ethylene Comonomer used Hexene Hexene Hexene Butene Butene Butene Run number and sample sequence Run 1-1 Run 1-2 Run 1-3 Run 2-1 Run 2-2 Run 2-3 Bed weight [kg] 79.6 78.5 76.0 88.9 80.7 76.0 Bed temperature [°C] 85 89 91 85 89 91 Residence time [hours] 3.0 2.8 2.8 3.0 3.0 2.9 Superficial gas velocity [m / s] 0.58 0.58 0.58 0.55 0.55 0.55 Total reactor pressure [kPa] 2390 2390 2390 2408 2410 2415 <![CDATA[C 2 Partial pressure [psia]]]> 200 200 200 200 200 200 <![CDATA[H 2 / C 2 Molar ratio [ppm / mol%]]]> 11.63 8.39 6.30 12.27 8.32 6.52 <![CDATA[C x / C 2 Molar ratio [mol / mol]]]> 0.0091 0.0067 0.0038 0.0332 0.0218 0.0112 <![CDATA[C 2 Concentration [mol%]]]> 55.3 55.3 55.4 54.9 55.1 54.9 <![CDATA[C x Concentration [mol%]]]> 0.5 0.4 0.2 1.8 1.2 0.6 <![CDATA[H 2 Concentration [ppm]]]> 644 464 349 674 458 358 <![CDATA[iC 5 Concentration [mol%]]]> 2.6 2.3 2.3 0.9 0.8 0.8 <![CDATA[N 2 Concentration [mol%]]]> 42 42 42 42 43 44 Production rate [kg / hr] 26.5 28.0 27.1 29.6 26.9 26.2
[0112] In Table 1, XCAT TMEZ-100 is a commercial bridged bis(tetrahydroindenyl)zirconocene catalyst from Univation Technologies, LLC (a wholly-owned subsidiary of The Dow Chemical Company, headquartered in Houston, Texas); hexene is 1-hexene; butene is 1-butene; kg / hr is kilograms per hour; kg is kilogram; kPa is kilopascal; m / s is meters per second; psia is pounds per square inch gauge + 1 atmosphere; C 2 is ethylene; H 2 is hydrogen; C x is comonomer; iC 5 is isopentane; N 2 is nitrogen; mol is mole; ppm is parts per million by weight; mol% is mole percentage.
[0113] The gas phase polymerization conditions in Table 1 indicate that the gas phase polymerization conditions, reactors, and bridged bis(tetrahydroindenyl)zirconocene catalysts can be used to prepare embodiments of the C4-uLLDPE copolymers of the present invention that cover the claimed resin property ranges.
[0114] The resin properties of Examples 1 to 3 of the present invention of C4-uLLDPE and Comparative Examples A to C of Comparative C6-uLLDPE prepared according to the gas phase polymerization conditions listed in Table 1 above are reported in Table 2 below.
[0115] Table 2: Characteristics of the inventive C4-uLLDPE and comparative C6-uLLDPE of the present invention:
[0116]
[0117] In Table 2, hexene means 1-hexene; butene means 1-butene; mono- means monomodal; g / 10min. means grams per 10 minutes; GPC Mw and GPC Mn mean weight average molecular weight and number average molecular weight, respectively, which are measured by the high temperature gel permeation chromatography test method described above; g / mol means grams per mole; Temp. means temperature; % means percentage; wt% means weight percentage; SCBI means short chain breadth index; and N / m means not measured.
[0118] The data in Table 2 indicate that the C4-uLLDPE of the present invention has basic resin properties suitable for melt processability, which is further confirmed by the data in Table 3 below.
[0119] Table 3: Film extruder production line parameters for preparing single-layer (1 layer) films 1 to 6:
[0120]
[0121] The film manufacturing conditions in Table 3 show that the inventive C4-uLLDPE resin has good melt processability, as indicated by a head pressure of less than 5,000 psi (less than 34.5 MPa), which enables the resin to be melt processed into very thin (0.025 mm thick) monolayer films without defects, i.e., bubble instability, thickness variation, wrinkles, lines, rough surface due to melt fracture, holes or tears. Therefore, the inventive C4-uLLDPE can be used to prepare monolayer films and multilayer films.
[0122] Table 4: Characteristics of single-layer films 1-6:
[0123]
[0124] In Table 4, g is gram; gf is gram-force; psi is pounds-force per square inch; and MPa is megapascals.
[0125] The data in Table 4 show the improved (increased) directional tear properties of the films of the present invention. This is illustrated by comparing the Elmendorf Tear MD value and the Elmendorf Tear CD value. The Elmendorf Tear MD property is a force measurement that can be used to characterize directional tear properties, which is the ability of the film to be torn in the machine direction. The lower the Elmendorf Tear MD value, the better the directional tear properties of the film. For example, by comparing the film of CE A and the film of IE1, the Elmendorf Tear Ratio CD / MD increases from 2.3 to 6.7, and by comparing CE B and IE 2, the Elmendorf Tear Ratio CD / MD increases from 5.7 to 12. The Elmendorf Tear Ratio CD / MD of CE C is already high at 15, and starting from CE C, the Elmendorf Tear Ratio CD / MD of IE 3 is reduced by 20% to a still desirable 12. The absolute value of the Elmendorf Tear MD of IE3 is improved (reduced) relative to CE C. Embodiments of the monolayer films of the present invention having a thickness of 0.0254 millimeters (mm; 1 mil) and prepared under the film manufacturing conditions described in the embodiments can be characterized as having an Elmendorf Tear MD of 15 grams force (gf) to 100 gf, alternatively 15 gf to 30 gf, alternatively 21 gf to 99 gf. In some embodiments, the improvement (increase) in directional tearing of the films of the present invention is characterized by any of the aforementioned Elmendorf Tear MD values combined with an Elmendorf Tear Ratio CD / MD of 6.1 to 13, alternatively 6.2 to 7.2, alternatively 11.5 to 12.5. Thus, the C4-uLLDPE resins of the present invention can be used to make blown LLDPE films with improved (increased) directional tearing. The films of the present invention are easy to tear in the machine direction (MD) or in the reverse machine direction (opposite to the MD), i.e., have a lower tear resistance, but are difficult to tear in the cross direction (CD, also known as the transverse direction (TD)) or in the reverse transverse direction.
[0126] The data in Table 4 also indicate that the C4-uLLDPE resins and films of the present invention have an overall toughness suitable for withstanding the abuse of articles made therefrom during transportation and handling. This is illustrated by the dart impact data and the MD and CD data for the 1% secant modulus, yield stress, yield strain, fracture stress, and fracture strain. For example, the yield stress CD is a pressure measurement that can be used to characterize the ability of a film to be manually stretched and wrapped around an object (such as a pallet stack of boxes) without breaking. The higher the pressure that can be withstood during stretching / wrapping, the greater the ability of the film to stretch / wrap without breaking. Embodiments of the monolayer films of the present invention having a thickness of 0.0254 mm (1 mil) and prepared under the film manufacturing conditions described in the examples can be characterized as having a yield stress CD of 11.7 megapascals to 20.7 megapascals (MPa; 1,700 psi to 3,000 psi), alternatively 15.1 MPa to 20.7 MPa (2,200 psi to 3,000 psi), alternatively 11.7 MPa to 15.9 MPa (1,700 psi to 2,300 psi). The fracture strain MD and fracture strain CD are percentage change measurements that can be used to characterize the ability of a film to be stretched to a longer length without breaking. These properties are valued by customers of stretch films as a way to compare different stretch film products. The higher the percentage of stretch achieved at break, the greater the stretchability of the film without breaking. Embodiments of the monolayer films of the present invention having a thickness of 0.0254 mm (1 mil) and prepared under the film manufacturing conditions described in the examples can be characterized as having a fracture strain CD (elongation at break CD) of 630% to 690%, alternatively 670% to 690%, alternatively 630% to 674%. Embodiments of the monolayer films of the present invention having a thickness of 0.0254 (1 mil) and prepared under the film manufacturing conditions described in the examples can be characterized as having a fracture strain MD (elongation at break MD) of 510% to 530%, alternatively 520% to 530%, alternatively 510% to 526%.
[0127] Accordingly, the C4-uLLDPE resins of the present invention can be manufactured to have good toughness, good melt processability, and films can be prepared that achieve the foregoing technical solutions. The C4-uLLDPE resins of the present invention have an overall toughness such that they can withstand the normal abuse of end-user operations (e.g., packaging operations such as wrapping a pallet of boxes with a film) and the transportation and disposal of end-user products (e.g., transporting and disposing of a pallet of goods in a package). The films of the present invention also have good optical clarity and haze. The films of the present invention will allow end-users such as consumers to be able to tear open a grocery bag, a wrapped package, or a container liner (such as a box or drum liner) by hand without the aid of a cutting blade and without an undesired tear in the vertical direction, which could result in the containment of the internal material.
Claims
1. A single-peak linear low-density ethylene / 1-butene copolymer, which is prepared by copolymerizing ethylene and 1-butene using a bridged bis(tetrahydroindenyl)zirconocene catalyst selected from the group consisting of: ethylene bis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, ethylene bis(4,5,6,7-tetrahydroindenyl)dimethylzirconium, dimethylsilyl bis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, dimethylsilyl bis(4,5,6,7-tetrahydroindenyl)dimethylzirconium, diphenylsilyl bis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, diphenylsilyl bis(4,5,6,7-tetrahydroindenyl)dimethylzirconium, diethylsilyl bis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, and diethylsilyl bis(4,5,6,7-tetrahydroindenyl)dimethylzirconium; wherein the single-peak linear low-density ethylene / 1-butene copolymer is characterized by each of the following properties: a density of 0.915 grams per cubic centimeter (g / cm 3 ) to 0.939 g / cm 3 measured according to Method B of ASTM D792-13; a melt index (I 2 ) of 0.1 grams per 10 minutes (g / 10 min.) to 4.0 g / 10 min. measured according to ASTM D1238-13 under the conditions of 190 °C / 2.16 kg; and a polydispersity index M w / M n of 3.0 to 5.0 measured according to the high-temperature gel permeation chromatography (GPC) test method in the specification.
2. The unimodal linear low density ethylene / 1-butene copolymer according to claim 1, wherein the unimodal linear low density ethylene / 1-butene copolymer has at least one of the characteristics (i) to (iv): (i) a density of from 0.921 g / cm 3 to 0.939 g / cm 3 ; (ii) a melt index (I 2 ) of from 0.2 g / 10 min. to 1.4 g / 10 min.; (iii) a polydispersity index M w / M n of from 3.5 to 4.5; and (iv) an LCB content of from 0.005 to 0.050 (content / 1000C) per 1000 carbon atoms as measured by carbon-13 nuclear magnetic resonance ( 13 C-NMR) spectroscopy according to the long chain branching (LCB) value test method in the specification.
3. The unimodal linear low density ethylene / 1-butene copolymer according to claim 1 or claim 2, characterized in that The following melt flow ratio (I 21 / I 2 ), at least one of (i) to (iii): (i) The melt flow ratio (I 21 / I 2 ), which is characterized by the following formula (A): The melt flow ratio (I 21 / I 2 ) is greater than (-36.9 * melt index (I 2 )) + 68.0 (EQ. (A)), where * indicates multiplication, + indicates addition, and the symbol for "greater than" is >; (ii) Melt flow ratio (I 21 / I 2 ), the melt flow ratio is characterized by the following formula (B): Melt flow ratio (I 21 / I 2 ) is less than (-36.9 * melt index (I 2 )) + 80.0 (EQ. (B)), where * indicates multiplication, + indicates addition, and the symbol for "less than" is <; and (iii) a melt flow ratio of 30 to 70 (I 21 / I 2 ); wherein the high load melt index (I 21 ) is measured according to ASTM D1238-13 using conditions of 190 °C / 21.6 kg, and the melt index (I 2 ) is measured according to ASTM D1238-13 using conditions of 190 °C / 2.16 kg.
4. The unimodal linear low density ethylene / 1-butene copolymer according to any one of claims 1 to 3, wherein the unimodal linear low density ethylene / 1-butene copolymer has a short chain branching distribution different from that of a reference unimodal linear low density ethylene / 1-hexene copolymer (reference EH copolymer, as defined herein), and the difference is designated δ(SCBD) and δ(SCBD) is greater than 3%.
5. A post-reactor blend comprising the unimodal linear low density ethylene / 1-butene copolymer according to any one of claims 1 to 4 and a different polyolefin polymer.
6. A film comprising the unimodal linear low density ethylene / 1-butene copolymer according to any one of claims 1 to 4 or the post-reactor blend according to claim 5.
7. The film according to claim 6, wherein the film is a single-layer film consisting of one layer, and wherein the one layer comprises the unimodal linear low density ethylene / 1-butene copolymer or the post-reactor blend.
8. The film according to claim 7, wherein the film is a multi-layer film consisting of 3 to 12 layers, and wherein at least one of the 3 to 12 layers comprises the unimodal linear low density ethylene / 1-butene copolymer or the post-reactor blend.
9. The film according to claim 6 or claim 7, wherein if the film has a thickness of 0.0254 mm (1 mil) and is prepared under the film manufacturing conditions described in the examples, the film is characterized by at least one of the limitations (i) to (iii): (i) A yield stress CD of 11.7 megapascals (MPa) to 20.7 MPa, (ii) A breaking strain CD (elongation at break CD) of 630% to 690%; and / or (iii) A breaking strain MD (elongation at break MD) of 510% to 530%.
10. A method for preparing a film, the method comprising: Extruding at least one melt of the unimodal linear low density ethylene / 1-butene copolymer according to any one of claims 1 to 4 or the post-reactor blend according to claim 5 as a film having at least one layer.
11. The method for preparing a film according to claim 10, wherein the film is a single-layer film, the method comprising: Extruding a melt comprising the unimodal linear low density ethylene / 1-butene copolymer or the post-reactor blend through a single die orifice to prepare the single-layer film.
12. The method for preparing a film according to claim 10, wherein the film is a multi-layer film, the method comprising: Extruding at least one melt comprising the unimodal linear low density ethylene / 1-butene copolymer or the post-reactor blend through different ones of from 3 to 12 die holes, and optionally extruding a melt comprising the unimodal linear low density ethylene / 1-butene copolymer, low density polyethylene, unimodal linear low density ethylene / 1-hexene copolymer or a post-reactor blend thereof through a different one of the die holes, to thereby prepare the multilayer film comprising from 3 to 12 layers.
13. A manufactured article, the manufactured article comprising an object and a film covering the object and having tear orientation and comprising the unimodal linear low density ethylene / 1-butene copolymer according to any one of claims 1 to 4.
Citation Information
Patent Citations
Ethylene / 1-butene copolymers with enhanced resin processability
US10370469B2
Low density polyethylene copolymer having excellent film processability and transparency
US10508164B2
Improvement in bridge-sates
US107119A
Mono-web directional tear packaging film
US20050100753A1
Unimodal polyethylene copolymer and film thereof
US20210070902A1